Multi-mode propagation and diffusion analysis using the three-dimensional second strain gradient elasticity. (15th March 2023) - Yang, Bo; Ichchou, Mohamed; Zine, Abdelmalek; Droz, Christophe
Abstract: The multi-mode propagation and diffusion properties are crucial informations when studying complex waveguides. In this paper, firstly, the three-dimensional modeling of micro-sized structures is introduced by using the second strain gradient theory. The constitutive relation is deduced while the six quintic Hermite polynomial shape functions are employed for the displacement field. The weak formulations including element stiffness and mass matrices and the force vector are calculated through the Hamilton's principle and the global dynamic stiffness matrix of a unit cell is assembled. Then, free wave propagation characteristics are analyzed by solving eigenvalue problems within the direct wave finite element method framework. The dispersion relations of positive going waves considering the size effects are illustrated. Furthermore, the effects of higher order parameters on the dispersion curves are discussed and the forced responses with two boundary conditions are expounded. Eventually, the wave diffusion including reflection and transmission coefficients are illustrated through simple and complex coupling conditions, respectively. The dynamic analysis of coupled waveguides through the wave finite element method equipped with the second strain gradient is a novel work. The results show that the proposed approach is of significant potential for investigating the wave propagation and diffusion characteristics of micro-sized structures. Highlights: Second strain gradient theory is used for the modeling of 3D micro-sized structures. Constitutive relation and weak forms are calculated through the Hamilton's principle. Wave propagation properties are analyzed within wave finite element method framework. Wave diffusion characteristics are illustrated through a simple and a complex coupling conditions.